ON THE KINETICS OF ION EXCHANGE IN PHLOGOPITE - AN IN SITU AFM STUDY - Aldushin K.; Jordan G.; Aldushina E.; Schmahl W.W. (My University, 2007)
The kinetics of cation exchange in phlogopite have been studied in situ by hydrothermal atomic force microscopy (HAFM). The exchange of interlayer K by octylammonium ions caused an increase in the interlayer distance and the formation of reaction fronts which can be locally resolved by AFM. The observed reaction fronts revealed substantial variations in their propagation rates — even within single interlayers. This observed variability in interlayer reactivity could mainly be attributed to chemical and structural inhomogeneities of the samples. A quantitative evaluation of the front propagation at representative sites yielded a diffusion coefficient of the K+ exchange by octylammonium of 1.2±0.6 × 10−11 cm2/s assuming negligible transport normal to the layers. The reverse reaction, i.e. the exchange of organic ions by K+, resulted in a retreat of the reaction fronts and a general restoration of the original morphological state. However, indications of structural alterations and areas with trapped octylammonium ions were found.
Keywords: ALKYLAMMONIUM; ATOMIC FORCE MICROSCOPY; CLAYS; CATION EXCHANGE; DIFFUSION; MICA; ORGANIC IONS; PHYLLOSILICATES; SURFACE ALTERATION; SWELLING